Promoting global gender-fair language in college English classrooms: A study of student awareness and usage in a state college - Judith, Vanessa Joy Z. (Edelweiss Applied Science and Technology, 2025)
The study investigates the level of awareness and extent of usage of gender-fair language (GFL) in English classroom instruction among Bachelor of Secondary Education (BSED) majors in English students at a state university in the Central Philippines. Using a descriptive-correlational design, the research employed a researcher-made instrument based on established GFL principles, collecting data from respondents selected via stratified random sampling. The primary aim was to examine overall awareness and use of GFL, as well as differences by sex and year, and to assess the relationship between awareness and use. Results indicated that students' awareness and usage of GFL were at least moderate, with female students showing significantly higher awareness than males. No significant sex difference was found in overall use. A statistically significant positive correlation was observed between awareness and usage, suggesting that higher awareness correlates with greater GFL practice. The study recommends expanding GFL in educational programs and extending institutional support to enhance inclusivity. These findings underscore the importance of language in shaping gender perceptions and the need for long-term gender-fair efforts in academic settings.